(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The introduction and the importance of the research include that leadership is one of the most important elements of human behavior. It has become an important factor in identifying civilization throughout the ages. In order to understand the past, we must study the leaders who shaped history. When we understand the present, we look at the past leaders and the present leaders. Leadership is of great importance to humanity, as leadership is one of the biggest needs in our time, and the researcher hopes, through this study, to reach results that have positive implications. On different aspects in sports measurements, and it will be a new link in the series of studies that preceded it and enhance its results and results. Measurements can also appear in the best organizations, and these results can open the building for sports movement and football. The research problem is in aerobic exercise The study included the research methodology and its field procedures, so the descriptive approach was adopted by the survey method to solve the problem, and the research sample was selected by the (intentional) method on club players, and the research sample included (169) players in the first and second divisions in Dhi Qar. It included several recommendations and conclusions, the most important of which are 1- Building a scale of transformational leadership among coaches of sports clubs from the point of view of soccer players 2- There is a clear discrepancy in the application of the scale of transformational leadership among coaches of sports clubs from the point of view of players in the first and second division clubs in Dhi Qar. As for the recommendations, they were among them Including. 1- Adopting the transformational leadership scale of the coaches of sports clubs from the point of view of the players. 2- The necessity of clear knowledge from the trainers of the importance of transformational leadership as a modern method in managing the training process and sports clubs.